2000
DOI: 10.1136/jcp.53.6.451
|View full text |Cite
|
Sign up to set email alerts
|

Immunoflow cytometry and cell block immunohistochemistry in the FNA diagnosis of lymphoma: a review of 73 consecutive cases

Abstract: Aims-To review the results of 73 consecutive fine needle aspirations (FNAs) that were collected by a pathologist and analysed by immunoflow cytometry. Material for a cell block was also collected from some of these lesions. Methods-The setting was a large general hospital in rural New Zealand. The FNAs were performed by a pathologist, or a radiologist for image guided localisations. Material for immunoflow cytometry was collected into RPMI and, when required, material for a cell block was collected into formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 8 publications
3
45
0
1
Order By: Relevance
“…Therefore, excisional biopsy is considered necessary by some authors to confirm these diagnoses (Metzgeroth et al, 2012); however, this is not always possible because of the poor general medical condition of these patients (Ahmed HG et al, 2013). Recent studies have indicated that an accurate diagnosis of lymphoproliferative disorders can be achieved by FNA in 85.9-87% of the cases, particularly when cytology is supported by flow cytometry and immunohistochemistry techniques, representing a powerful first-choice diagnostic technique (Mayall and Dray, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, excisional biopsy is considered necessary by some authors to confirm these diagnoses (Metzgeroth et al, 2012); however, this is not always possible because of the poor general medical condition of these patients (Ahmed HG et al, 2013). Recent studies have indicated that an accurate diagnosis of lymphoproliferative disorders can be achieved by FNA in 85.9-87% of the cases, particularly when cytology is supported by flow cytometry and immunohistochemistry techniques, representing a powerful first-choice diagnostic technique (Mayall and Dray, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[13][14][15] The possibility of applying a complete panel of antibodies and diagnostic algorithms is the most appreciated advantage of the technique; 4,6,8 consequently, many reports stress the high sensitivity in detecting non-Hodgkin lymphoma (NHL) through the combined application of FNC and FC. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The most enthusiastic reports hypothesize that, in the near future, histology will not be necessary strictly for the diagnosis of NHL. In fact, in many institutions, FNC coupled with ancillary techniques like FC routinely has replaced histology in the diagnosis of recurrent NHL (rNHL).…”
mentioning
confidence: 99%
“…It is, however, limited by the inability to identify a small population of neoplastic cells from among reactive cells and as such could not be used in HL or TCRBL. 17,27,33 Nevertheless, flow cytometry can detect the deletion of certain antigens (such as CD4 and CD5), thereby assisting in the diagnosis of PTCL. 34 Immunocytochemistry on cytospin material, while useful in many cases, 16 suffers from the potential drawback of having to work on ruptured tumor cells.…”
Section: Discussionmentioning
confidence: 99%